Evidence of the reliability and validity of the MAYSI-2 in a Spanish sample of minors serving therapeutic judicial measures - Pugliese, Antonella; Hess-Medler, Stephany; Martín, Ana M. (Anales de Psicología / Annals of Psychology, 2025)
The Spanish juvenile justice system provides for the assignment of therapeutic internment and outpatient treatment measures for cases with mental health needs. The purpose of this study is to provide evidence of internal consistency and validity of the Massachusetts Youth Screening Instrument: Second version (MAYSI-2), a screening instrument for mental health needs designed for juvenile justice and translated into several languages, including Spanish. The sample consisted of 126 Spanish adolescents, mostly male, between 15 and 21 years of age, who were serving therapeutic judicial measures. In addition to the Spanish translation of the MAYSI-2, the Spanish adaptations of the MACI and the YLS/CMI were applied. The results obtained support the use of the MAYSI-2 translation in the Spanish juvenile justice system, since the original seven-factor structure is replicated in the sample under study. Evidence was also found of convergent validity, with respect to the conceptually related scales of the MACI, and of divergent validity, regarding the risk factors of the YLS/CMI. Finally, evidence of discriminant validity was obtained, referring to the type of judicial therapeutic measure, the existence of a psychopathological diagnosis and the risk of recidivism.